A Case for a History of Ordinary Lives - Gil Montero, Raquel (2020)
What is "normal" does not leave major traces. The historiography on colonial Andes is mostly based on trials and petitions, the most detailed sources that historians have to reconstruct the lives of indigenous people, since they include at least part of their voices. However, they show the perspective of native authorities, of exceptional people who wrote or initiated trials, or of people during special conjunctures, such as the rebellions. With this case, I propose sources that show the traces of the normal, especially the traces left in those places where native authorities were not important, where trials were just a few or limited to some specific events, or where the "moral economy" was not altered.